Use of composite voxels in FFT based elastic simulations of hollow glass microspheres/polypropylene composites. (January 2020) - Charière, Romain; Marano, Aldo; Gélébart, Lionel
Highlights: FFT solver with composite voxels applied to thin shell HGM-thermoplastic composite. Composite voxels : a requirement for evaluating HGM/matrix interface stresses. Application to a real microstructure and comparison with experimental results. Statistical description of the interfacial normal stresses. Abstract: Thermoplastic polymer composites filled with hollow glass microspheres (HGM) are of growing interest as lightweight materials. In order to better understand the relationship between the microstructure and the mechanical properties, Finite Element simulations based on the microstructure are now commonly performed. However, their computational cost becomes prohibitive when increasing the size and mesh refinement of the simulated unit cell. Massively parallel FFT-based solvers allow to overcome those limitations. The main purpose of the paper is to demonstrate that FFT-based solvers can be used to simulate HGM-thermoplastic composites, focusing on both the average behavior and the distribution of normal stresses at HGM-matrix interface. Actually, in addition to infinite elastic contrasts, the thin thickness of the HGM glass shell raises a problem, as well as the evaluation of interfacial stresses from a grid-based discretization. These problems are alleviated by using composite voxels (i.e. an homogenization rule is used for voxels crossed by an interface). The numerical study is supported by experiments (microstructure and mechanical characterization) performed on polypropylene composites with various HGM contents. Finally, an original statistical description of the interfacial normal stresses is proposed, gathering the results obtained on a large number of spheres.